An Unusual Presentation of Spinal Giant Cell Glioblastoma in a 21-Year-Old Female - Benjamin J. Delgado BS; Leila Moosavi MD; Ericka Rangel BS; William Stull MD; Rahul Dev Polineni MD; Joseph Chen MD; Everardo Cobos MD (SAGE Publishing, 2019)
Primary spinal cord giant cell glioblastoma multiforme of the thoracic spinal cord is a rarely-diagnosed primary spinal cord tumor in comparison to neoplasms in intracranial locations. In this article, we highlight a young adult who was diagnosed with intramedullary giant cell glioblastoma, IDH wild-type, World Health Organization grade IV/IV of the thoracic spinal cord. This case report describes the treatment approach with a postsurgical combination of radiation therapy and temozolomide, which resulted in the patient to return to her baseline of health only to later develop neurological symptoms significant for a recurrence of malignancy. In a review of the literature of described cases of primary spinal cord glioblastoma multiforme, prognosis continues to be unfavorable as current treatment options of the aggressive malignancy remain absent of a cure.